2023
DOI: 10.1158/1078-0432.ccr-22-2903
|View full text |Cite
|
Sign up to set email alerts
|

Liquid Biopsy of Cerebrospinal Fluid Enables Selective Profiling of Glioma Molecular Subtypes at First Clinical Presentation

Abstract: Purpose: Current glioma diagnostic guidelines call for molecular profiling to stratify patients into prognostic and treatment subgroups. In case the tumor tissue is inaccessible, cerebrospinal fluid (CSF) has been proposed as a reliable tumor DNA source for liquid biopsy. We prospectively investigated the use of CSF for molecular characterization of newly diagnosed gliomas. Experimental design: We recruited two cohorts of newly diagnosed glioma patients, one (n=45) providing CSF collected in proximity of the t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 39 publications
(41 reference statements)
0
19
0
Order By: Relevance
“…This highly sensitive technique successfully detected ctDNA targeting H3 K27M and pTERT mutations in gliomas [ 56 , 76 , 83 , 98 , 99 ]. Table 1 summarizes the representative studies utilizing digital PCR on CSF and shows that digital PCR can detect variant alleles with a high sensitivity of 70–100% in glioblastoma and 80–100% in DMG [ 13 , 56 , 76 , 83 , 92 , 93 , 100 ]. However, even with digital PCR using CSF, the detection of low-grade gliomas is challenging, as they are generally detected in less than 50% of cases, and in some cases, they are not identified at all.…”
Section: Methodology Of Liquid Biopsy Using Cell-free Dnamentioning
confidence: 99%
“…This highly sensitive technique successfully detected ctDNA targeting H3 K27M and pTERT mutations in gliomas [ 56 , 76 , 83 , 98 , 99 ]. Table 1 summarizes the representative studies utilizing digital PCR on CSF and shows that digital PCR can detect variant alleles with a high sensitivity of 70–100% in glioblastoma and 80–100% in DMG [ 13 , 56 , 76 , 83 , 92 , 93 , 100 ]. However, even with digital PCR using CSF, the detection of low-grade gliomas is challenging, as they are generally detected in less than 50% of cases, and in some cases, they are not identified at all.…”
Section: Methodology Of Liquid Biopsy Using Cell-free Dnamentioning
confidence: 99%
“…These findings are particularly crucial for patients with tumors in locations inaccessible to surgical biopsy or those who cannot undergo such procedures due to medical comorbidities. 76 However, the application of CSF-based liquid biopsies in clinical practice is at a nascent stage, with several challenges that need addressing. The invasiveness of CSF collection, typically through lumbar puncture, poses risks and could limit the frequency of sampling.…”
Section: Cerebrospinal Fluid In Liquid Biopsy For Brain Cancermentioning
confidence: 99%
“…For example, studies have reported the successful identification of key mutations in CSF from glioma patients, providing actionable insights into tumor genomics. These findings are particularly crucial for patients with tumors in locations inaccessible to surgical biopsy or those who cannot undergo such procedures due to medical comorbidities 76 …”
Section: Clinical Applications and Case Studies In Diverse Fluidsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sensitive and molecular assays enable enhancements and higher detectable rates. [85] CSF Diagnostic yield may be improved by identification of Clonal IGH rearrangements. This refers to specific rearrangements of immunoglobulin heavy chain gene, they are produced by B-cells.…”
Section: Limitations Of Csf Liquid Biopsymentioning
confidence: 99%